Identification of the First De Novo UBIAD1 Gene Mutation Associated with Schnyder Corneal Dystrophy - Benjamin R. Lin; Ricardo F. Frausto; Rosalind C. Vo; Stephan Y. Chiu; Judy L. Chen; Anthony J. Aldave (Journal of Ophthalmology)
Purpose. To report the identification of the first de novo UBIAD1 missense mutation in an individual with Schnyder corneal dystrophy (SCD). Methods. A slit lamp examination was performed on a 47-year-old woman without a family history of corneal disorders. The proband’s parents, two sisters, and son were also examined and genomic DNA from all six individuals was collected. The exons and exon-intron boundaries of UBIAD1 were screened using Sanger sequencing. Identified mutations were screened for in 200 control chromosomes. In silico analysis predicted the impact of identified mutations on protein function and structure. Results. Slit lamp examination of the proband revealed findings consistent with SCD. Corneas of the family members appeared unaffected. Screening of UBIAD1 in the proband identified a novel heterozygous c.308C>T mutation, predicted to encode the missense amino acid substitution p.(Thr103Ile). This mutation was not identified in any of the family members or in 200 control chromosomes and was predicted to be damaging to normal protein function and structure. Conclusions. We present a novel heterozygous de novo missense mutation in UBIAD1, p.(Thr103Ile), identified in a patient with classic clinical features of SCD. This highlights the value of genetic testing in clinical diagnostic settings, even in the absence of a positive family history.